1975
DOI: 10.1007/bf01531771
|View full text |Cite
|
Sign up to set email alerts
|

The environmental movement and its critics

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Springer is collaborating with JSTOR to digitize, preserve and extend access to Human Ecology.http://www.jstor.org The history and nature of the new environmental movement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 35 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…A measure of national population, from the Arthur Banks Cross National Time Series Data Archive, 52 was used as a control 98 • From Science to Multiculturalism 51.Snow 1992, 49;and Sills 1975; but also seeMorrison and Dunlap 1986. 52.…”
mentioning
confidence: 99%
“…A measure of national population, from the Arthur Banks Cross National Time Series Data Archive, 52 was used as a control 98 • From Science to Multiculturalism 51.Snow 1992, 49;and Sills 1975; but also seeMorrison and Dunlap 1986. 52.…”
mentioning
confidence: 99%
“…Some of them connect attitudes toward open space with class anxieties. Neuhaus writes (Sills 1975), Conservation has been historically and remains an upper class anxiety. The very rich fret about their game or the preservation of their estates.…”
Section: Open Space Value Pluralismmentioning
confidence: 98%
“…Lester (1990) maintains that wealth is a strong predictor of environmental policy. Indeed, numerous studies have found environmental support to be more likely among mid-and upper-class individuals than those defined as lower class (Baldassare 1986;Beckerman 1975;Neuhaus 1971;Sills 1975). Interestingly however, it may not be "wealth," per se, that underlies the phenomenon.…”
Section: Environmental Agendamentioning
confidence: 99%